Analysis of Morton Effect Induced Vibration based on Transfer Function Model: Influence of L/D ratio of Journal Bearing and Rotational speed. Issue 1 (May 2021) - Suzuki, Takafumi; Chiba, Jotaro; Yabui, Shota; Tomimatsu, Shigeyuki; Inoue, Tsuyoshi
Abstract: The Morton effect is the vibration phenomena that occur due to a thermal imbalance in the oil film in the journal bearing. In previous studies, the qualitative evaluation was performed based on theoretical modeling and numerical simulation. On the other hand, authors proposed that the characteristic of the journal bearing was considered as a proportional differential controller from a control engineering point of view. In the proposed model, the vibration due to the Morton effect can be evaluated based on the transfer function models. The proposed model is based on frequency characteristics identified from the experimental data directly, therefore, the model can be easily applied to the actual rotating machineries. The authors focus this study on applying the proposed method to the actual design, and investigated the relationship of the parameters of the transfer function between the L/D ratio and rotating speed. The relationship indicates the degree of influence of the L/D ratio and rotating speed to the vibration due to the Morton effect. The author measured the vibration by arbitrarily setting the L/D ratio, and analyzed the influence to the vibration due to the Morton effect based on the transfer function model. As a result, the author was able to predict the influence of the bearing L/D and rotating speed on the Morton effect.